Salvianolic Acid A Ameliorates Arsenic Trioxide-Induced Cardiotoxicity Through Decreasing Cardiac Mitochondrial Injury and Promotes Its Anticancer Activity - Zhang, Jing-yi; Wang, Min; Wang, Rui-ying; Sun, Xiao; Du, Yu-yang; Ye, Jing-xue; Sun, Gui-bo; Sun, Xiao-bo (Frontiers in Pharmacology, 2018)
Arsenic trioxide (ATO) is used as a therapeutic agent in the treatment of acute promyelocytic leukemia (APL). The therapeutic use of arsenic is limited due to its severe cardiovascular side effects. The cardio-protective effect of salvianolic acid A (Sal A) against ATO cardiotoxicity has been reported. However, the distinct role of the mitochondria in the cardio-protection of Sal A is not understood. The aim of this study was to determine whether Sal A preconditioning protects against ATO-induced heart injury by maintaining cardiac mitochondrial function and biogenesis. For the in vivo study, BALB/c mice were treated with ATO and/or Sal A. For the in vitro study, we determined the effects of ATO and/or Sal A in H9c2 cardiomyocytes. Our results showed that ATO induced mitochondrial structural damage, abnormal mitochondrial permeability transition pore (mPTP) opening, overproduction of mitochondrial reactive oxygen species (ROS), and decreased the ATP content. Sal A pretreatment alleviated the ATO-induced mitochondrial structural and functional damage. In this study, ATO decreased the expression level of the peroxisome proliferator activator receptor gamma-coactivator 1(PGC-1α) and disrupted the normal division and fusion of mitochondria. Sal A pretreatment improved the dynamic balance of the damaged mitochondrial biogenesis. Moreover, the combination treatment of Sal A and ATO significantly enhanced the ATO-induced cytotoxicity of SGC7901, HepaRG, K562 and HL60 cells in vitro. These results indicated that Sal A protects the heart from ATO-induced injury, which correlates with the modulation of mitochondrial function, and the maintenance of normal mitochondrial biogenesis.